Penerapan Media E-Learning Berbasis Moodle pada Jurusan Teknik Informatika dan Sistem Informasi Universitas Trisakti - Gatot Budi Santoso; Frisca Adiesthy Irdiani; Nita Chairunnisa; Tondi Mulia Sinaga (Sekolah Tinggi Teknik - PLN, 2019)
This study aims to apply to moodle e-learning to Trisakti University students majoring in informatics engineering and information systems, knowing the feasibility of e-learning produced as a source of student learning, and revealing the effectiveness of e-learning towards the achievement of student learning outcomes. This study shows that e-learning was developed with Moodle through three stages, namely: first planning, design, and development, both e-learning are feasible to use for students, and the third is the application of e-learning to Trisakti University students majoring in informatics engineering and systems information effectively improves student cognitive learning outcomes. This is evidenced by a survey conducted by the author.